Surveillance of psychogenic adverse events following immunization in Zhejiang, China, 2020–2023 - Xuejiao Pan; Xiaohua Qi; Yaping Chen; Hui Liang (BMC Public Health)
Abstract Background Adverse events following immunization (AEFIs) refer to any untoward medical occurrence that follows immunization. Despite the large number of studies reporting various types of AEFIs worldwide, information on the psychogenic AEFIs remains scarce. Objective To describe the frequency and characteristics of psychogenic AEFIs among vaccine recipients in Zhejiang Province, China, from 2020 to 2023. Methods Psychogenic AEFIs in Zhejiang Province from January 1, 2020, to December 31, 2023, were collected through the Chinese National AEFI Information System (CNAEFIS) for a descriptive epidemiological analysis. Results From 2020 to 2023, a total of 421 cases of psychogenic AEFIs were reported in Zhejiang Province, accounting for 0.47% of all AEFI cases and corresponding to an incidence rate of 1.48/1 million doses. 74.82% of the psychogenic AEFIs were related to the coronavirus disease 2019 (COVID-19) vaccine, and 93.82% occurred on the day of vaccination. The common symptoms of psychogenic AEFIs included headache/dizziness, chest tightness/chest pain, fatigue/drowsiness, paleness, cold/chill, and nausea/vomiting. In addition, the distribution of psychogenic AEFIs varied significantly by gender, age, occupation, season, and location. Conclusions The overall incidence of psychogenic reactions after vaccination in Zhejiang Province is low, which is relatively higher in females and students. Monitoring, identification, evaluation, and response are required after new vaccines are launched and vaccine strategies are adjusted.